Short‐ and long‐term outcome in cats diagnosed with pyothorax: 47 cases (2009‐2018). (19th March 2021) - Krämer, F.; Rainer, J.; Bali, M. S.
Abstract : Objectives: The aims of this retrospective study were to report the short‐ and long‐term outcome in cats treated for pyothorax and to identify prognostic indicators as well as determine recurrence rate. Methods: Medical records from April 2009 to August 2018 were retrospectively reviewed. Cases were included if a diagnosis of pyothorax was confirmed via cytology and/or culture of pleural fluid. Cats diagnosed with or suspected of having other thoracic diseases and cats with no evidence of pleural effusion were excluded from the study. Results: Fifty‐five cats met the inclusion criteria. Eighty five percent (n=47) cats underwent medical management with thoracostomy tubes, pleural lavage and broad‐spectrum antibiotics. Fifteen percent (n=5) cases failed medical treatment and underwent thoracotomy. Twenty eight percent (n=13) did not survive to hospital discharge. Short‐term survival (14 days) was achieved in 72% (n=34). Long‐term follow‐up was available for 31 of 34 with a long‐term survival rate of 68% (n=30). The recurrence rate was 6% (n=2). Conclusion: For cats with pyothorax that survive to discharge the prognosis is excellent and the condition is associated with a low recurrence rate.